The Effects of Task-Based Process Writing Approach on the Academic Writing Skills among Second Language Tertiary Learners - Johari, Siti Katijah (Journal of ELT Research, 2018)
Academic writing occupies a very important place in the English language syllabus at tertiary level. Where higher institution writing is concerned, it is not enough that students have to write in traditional essay or report formats; their writing must be appropriate to the discipline – yet deal with the multitude of genres expected of them. Additionally, academic writing skill is considered an essential skill for academic success and a requirement for many occupations and professions. However, it is a skill that a number of second language tertiary students find most difficult to acquire and only a few of them fully master it. This study, therefore, embarks on the theory that task-based approach together with the exposure of process writing would have a significant influence on the development of students’ academic writing skills. In this study students were made to work in groups on real-life tasks which relate to their field of study or future employment. In the midst of pursuing the group project, the students will have to write their group proposal and individual writing assignment. This will be the stage where the process writing techniques are put into practice. This paper will illustrate an eclectic pedagogic intervention in the teaching of academic writing skills to second language tertiary students.  Keywords: academic writing, task-based approach, process writing approach, tertiary learners